Harnessing Carbon Trading and Life Cycle Assessments for Renewable Energy Transition in Southeast Asia - Hendriarto, Stevanus; Manap, Yusril Sudiro Abdul; Runtukahu, Yussuf Eddo; Utomo, Romualdus Nugraha Catur (Indonesian Journal of Energy, 2025)
The climate crisis, caused by fossil fuel dependence and deforestation, poses significant socio-economic and environmental challenges for Southeast Asia, including reduced agricultural productivity and increased health risks. Our study aims to fill this gap by assessing how renewable energy can mitigate these impacts, focusing on the region's potential and the mechanisms needed to support this energy transition. Through a structured review of peer-reviewed articles, government reports, and data from intergovernmental organizations, we analyzed Southeast Asia's renewable energy potential and the roles of carbon trading and life cycle assessments (LCA) as enabling mechanisms. Our findings reveal that, despite projected increases in CO? emissions from 1.4 gigatons (Gt) in 2018 to nearly 2.4 Gt by 2040, Southeast Asia has set ambitious targets to reduce energy consumption by 23% and increase renewable energy to 22.1% within the same timeframe. Achieving these goals will require robust, adaptive policies that incentivize renewable investment and promote regional cooperation. Carbon trading and LCA are identified as pivotal tools, providing financial motivation for emission reductions and offering frameworks to assess the environmental impacts of energy projects. In conclusion, this study suggests that Southeast Asia’s renewable energy adoption, supported by sustainable practices like carbon trading and LCA, could significantly advance both global climate mitigation and socio-economic resilience within the region.